2015
DOI: 10.1186/s12958-015-0061-9
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood adipokines, neonatal anthropometrics and postnatal growth in offspring of Hispanic and Native American women with diabetes mellitus

Abstract: BackgroundOffspring of women with diabetes mellitus (DM) during pregnancy have a risk of developing metabolic disease in adulthood greater than that conferred by genetics alone. The mechanisms responsible are unknown, but likely involve fetal exposure to the in utero milieu, including glucose and circulating adipokines. The purpose of this study was to assess the impact of maternal DM on fetal adipokines and anthropometry in infants of Hispanic and Native American women.MethodsWe conducted a prospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 31 publications
1
39
5
1
Order By: Relevance
“…In non‐stratified analyses, cord blood adiponectin has been positively associated with the SSF/TSF ratio at age 3 in Project Viva, with body composition at age 3 in twins and with fat mass at 2 weeks but not 3 months in offspring of African American women . In addition, authors of a study in Oklahoma reported that cord blood levels of high molecular weight adiponectin were positively associated with three measures of adiposity (SSF, body weight and percent fat) in male and female infants at 1 month of age . Null findings between adiponectin and multiple anthropometric measures (eg, BMI z‐score and fat mass) have also been observed at age 9 and age 5 .…”
Section: Discussionmentioning
confidence: 52%
“…In non‐stratified analyses, cord blood adiponectin has been positively associated with the SSF/TSF ratio at age 3 in Project Viva, with body composition at age 3 in twins and with fat mass at 2 weeks but not 3 months in offspring of African American women . In addition, authors of a study in Oklahoma reported that cord blood levels of high molecular weight adiponectin were positively associated with three measures of adiposity (SSF, body weight and percent fat) in male and female infants at 1 month of age . Null findings between adiponectin and multiple anthropometric measures (eg, BMI z‐score and fat mass) have also been observed at age 9 and age 5 .…”
Section: Discussionmentioning
confidence: 52%
“…Mothers and offspring were enrolled into a prospective longitudinal study on the impact of in utero exposure to diabetes, as previously described [27]. Gestational and type 2 diabetes in the mothers was diagnosed according to ADA guidelines [28].…”
Section: Methodsmentioning
confidence: 99%
“…Adiponectin and leptin are factors known to influence normal and abnormal fetal growth (10,11,12). Low adiponectin concentrations have been reported in adults and in infants who were born small for gestational age, linking growth restriction with a cardiometabolic profile later in life (13).…”
Section: Introductionmentioning
confidence: 99%